(untitled) (Agricultural Engineering, 2018)
Electromagnetic energy can alter metabolic and biosynthetic processes and under certain parameters of pulsed EMF it can change pulse repetition frequency, operation cycle, power, exposure, as well as it can slow down and inhibit cell growth. MW irradiation range of RNA and DNA – containing virus reduces their infectivity. Inhibition of bacterial cultures growth, changes in phagocytic activity of protein biosynthesis, ultrastructural changes in the cells when exposed to EMF EHF. It was found in experiments with micro-organisms that biological effects of EMF on microorganisms wore a resonant character. One of the basic mechanisms of inhibitory action of EHF radiation on harmful microorganisms is the role of membranes in biological reactions of microorganisms on the EMR.